A National Wastewater Monitoring Program for a better understanding of public health: A case study using the Australian Census. (January 2019) - O'Brien, Jake W.; Grant, Sharon; Banks, Andrew P.W.; Bruno, Raimondo; Carter, Stephen; Choi, Phil M.; Covaci, Adrian; Crosbie, Nicholas D.; Gartner, Coral; Hall, Wayne; Jiang, Guangming; Kaserzon, Sarit; et al.
Abstract: Wastewater contains a large range of biological and chemical markers of human activity and exposures. Through systematic collection and analysis of these markers within wastewater samples it is possible to measure the public health of whole populations. The analysis of effluent and biosolids can also be used to understand the release of chemicals from wastewater treatment plants into the environment. Wastewater analysis and comparison with catchment specific data (e.g. demographics) however remains largely unexplored. This manuscript describes a national wastewater monitoring study that combines influent, effluent and biosolids sampling with the Australian Census. An archiving program allows estimation of per capita exposure to and consumption of chemicals, public health information, as well as per capita release of chemicals into the environment. The paper discusses the study concept, critical steps in setting up a coordinated national approach and key logistical and other considerations with a focus on lessons learnt and future applications. The unique combination of archived samples, analytical data and associated census-derived population data will provide a baseline dataset that has wide and potentially increasing applications across many disciplines that include public health, epidemiology, criminology, toxicology and sociology. Graphical abstract: Unlabelled Image Highlights: Framework for national wastewater sampling to measure public and environment health Aligned wastewater influent, effluent and biosolid sampling and archiving with census Developed a questionnaire to characterise wastewater catchments and treatment plant processes Defined recruitment strategies to achieve comprehensive population coverage Matched census data will enhance interpretation of wastewater sample analysis.